Understanding Academic Misconduct - Hughes, Julia M. Christensen; McCabe, Donald L. (Canadian Journal of Higher Education, 2006)
Research suggests that the majority of U.S. undergraduate students have engaged in some form of misconduct while completing their academic work, despite knowing that such behaviour is ethically or morally wrong. U.S.-based studies have also identified myriad personal and institutional factors associated with academic misconduct. Implicit in some of these factors are several institutional strategies that may be implemented to support academic integrity: revisiting the values and goals of higher education, recommitting to quality in teaching and assessment practice, establishing effective policies and invigilation practices, providing educational opportunities and support for all members of the university community, and using (modified) academic honour codes. There is a dearth of similar research in Canada despite growing recognition that academic misconduct is a problem on Canadian campuses. This paper suggests that Canadian higher education can learn much from the U.S. experience and calls for both a recommitment to academic integrity and research on academic misconduct in Canadian higher education institutions.